A retrospective description of blood and urine alterations in 386 male cats with urethral obstruction in Botucatu, São Paulo, Brazil - de Moraes, Reiner Silveira [UNESP]; Ribeiro, Diego [UNESP]; Melchert, Alessandra [UNESP]; García, Henry David Mogollón; Regalin, Doughlas; Filho, Raphael Lúcio Andreatti [UNESP]; Takahira, Regina Kiomi [UNESP]; Giuffrida, Rogério; Okamoto, Adriano Sakai [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP] (My University, 2024)
Background: Urinary retention in obstructed male cats leads to changes in blood and urine compounds, which, combined with the time of obstruction, are linked to the worsening of the animal’s clinical status. Aim: This study aimed to describe the primary laboratory changes in male cats with urethral obstruction (UO). Methods: Medical records of 386 male cats diagnosed with UO and treated at the Veterinary Teaching Hospital of the Faculty of Veterinary Medicine and Zootechnics (FMVZ), UNESP—Botucatu, between 2010 and 2020 were reviewed. Data on sex, age, breed, body weight, and reproductive status were evaluated. Results: Over the years, complete blood count, renal and hepatic biochemistry, blood gas analysis, electrolytes, urinalysis, and urine culture were performed upon request. Anaemia was not representative in obstructed cats. Thrombocytopenia was identified in 65.5% (169/258) of patients, and neutrophilic leukocytosis was identified in 52.4% (170/326) of patients. High urea and creatinine values were detected in 82.9% (273/329) and 77.1% (256/331) of the patients, respectively. Acidemia, increased PO2, metabolic acidosis, hypochloremia, hyperkalemia, hypernatremia, and hypocalcemia were observed in 37.6% (90/239), 51.5% (120/233), 69.3% (160/231), 50.2% (115/229), 58.5% (138/239), 40.2% (93/231), and 85.7% (84/98) of the cats, respectively. Urinalysis revealed an acidic pH, isosthenuria, a low proportion of proteins, and a high presence of occult blood and erythrocytes per field (>1,000). Finally, 19.49% had positive cultures. Escherichia coli and Staphylococcus spp. are commonly isolated. Conclusion: This study provides a description of laboratory changes and those most prevalent in the population under study. UO may result mainly in isolated or combined laboratory changes such as azotemia, acidemia, metabolic acidosis, hyperkalemia, hypocalcemia, acidic pH, and occult blood in the urine. Additional laboratory changes may be present; however, they must be deeply investigated as comorbidities might be associated with them. Therefore, the description of laboratory changes in large populations, such as in male cats with UO, provides a reference for veterinarians regarding the hematological and urinary changes expected in obstructed male cats and instigates the search for further studies in the field.
Keywords: Blood abnormality; Felis catus; FLUTD; Urethra; Urine blockage